Analysis Of The Effect Of Soil Water Taking On Potential Of Soil Water Pollution In Semarang - Edy Suhartono; Royswan Isgandhi; Sriwahyuningsih Sulaiman; Pentardi Rahardjo; Lilik Satriyadi (Politeknik Negeri Semarang, 2019)
The city of Semarang is located on the beach and has a unique topography because it is divided into lowlands and highlands. To meet freshwater needs, groundwater extraction is generally carried out of confined aquifers. Related to population growth in urban coastal areas,has direct relationship with groundwater extraction to meet the needs of population activities such as industrial activities, services, and trade. The purpose of this study was to identify groundwater pollution with indicators of the content of chloride (Cl) concentrations in confined aquifers. This study uses quantitative descriptive analysis through survey techniques. In 2013, five out of seven villages experienced sea water intrusion with the highest chloride (Cl) levels of 293 mg/L in Sekayu, and in Panggung Kidul Village with the highest chloride of 2,020 mg/L was found. In this study of how intrusion on confined aquifers must be controlled using efficiency programs in water management.